X‐linked thrombocytopenia with thalassemia displays bone marrow reticulin fibrosis and enhanced angiogenesis: Comparisons with primary myelofibrosis. Issue 3 (16th January 2015) - Åström, Maria; Hahn‐Strömberg, Victoria; Zetterberg, Eva; Vedin, Inger; Merup, Mats; Palmblad, Jan
<x xml:space="preserve">Abstract</x> X‐linked thrombocytopenia with thalassemia (XLTT) is caused by the mutation 216R > Q in exon 4 of the GATA1 gene. Male hemizygous patients display macrothrombocytopenia, splenomegaly, and a β‐thalassemia trait. We describe two XLTT families where three males were initially misdiagnosed as having primary myelofibrosis (PMF) and all five investigated males showed mild‐moderate bone marrow (BM) reticulin fibrosis. Comparative investigations were performed on blood samples and BM biopsies from males with XLTT, PMF patients and healthy controls. Like PMF, XLTT presented with high BM microvessel density, low GATA1 protein levels in megakaryocytes, and elevated blood CD34+ cell counts. But unlike PMF, the BM microvessel pericyte coverage was low in XLTT, and no collagen fibrosis was found. Further, as evaluated by immunohistochemistry, expressions of the growth factors VEGF, AGGF1, and CTGF were low in XLTT megakaryocytes and microvessels but high in PMF. Thus, although the reticulin fibrosis in XLTT might simulate PMF, opposing stromal and megakaryocyte features may facilitate differential diagnosis. Additional comparisons between these disorders may increase the understanding of mechanisms behind BM fibrosis in relation to pathological megakaryopoiesis. Am. J. Hematol. 90:E44–E48, 2015. © 2014 Wiley Periodicals, Inc.